Modified technique for laparoscopic running vesicourethral anastomosis - Golabek, Tomasz (Termedia Publishing House, 2014)
INTRODUCTION: A vesicourethral anastomosis is the most challenging and time-consuming step of radical prostatectomy. In 2003, van Velthoven introduced his own technique of connecting the bladder neck with the membranous urethra, which has remained the most popular method since. Despite being effective, this method is time consuming and is not free from the risk of complications. AIM: Here we describe our technique for laparoscopic vesicourethral anastomosis using a running suture as an alternative to the traditional approach. MATERIAL AND METHODS: The vesicourethral anastomosis is created using a running stitch placed first at the 5 o'clock position on the posterolateral aspect of the bladder outside-in and then through the urethra at the same location inside-out. Proceeding anticlockwise, the running suture is placed 5 times more through both the bladder neck and the urethra in a similar fashion until it meets the free end at the 5 o'clock position. A single knot is then tied outside the bladder. RESULTS: The anastomotic technique has been used in 28 patients with clinically organ confined prostate cancer. The mean anastomosis time was 9.53 min, the mean operative time was 155.20 min, the mean drain permanence was 2.71 days, and the mean catheterisation time was 17.28 days. Continence rate 3 months after surgery was 92.85%, and 100% at 6- and 12-month follow-up visits. CONCLUSIONS: We describe a safe, feasible and efficient technique for vesicourethral anastomosis. Further studies on a larger group of patients are needed to confirm our encouraging preliminary results.